The Influence of Halal Labels, E-Wom (Electronic Word Of Mouth) and Customer Loyalty Towards the Decision to Purchase Halal Food on Shopee Food - Puspita, Arwiny; Ryan Andni (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2024)
Introduction: Halal labels are all products that have permission to be traded and have met Islamic law, this halal label is issued by the MUI agency. The purpose of this study was to determine the influence of halal labels, E-Wom (Electronic Word Of Mouth), and customer loyalty on purchasing decisions. Methods: This study uses quantitative research based on research data taken in the form of numbers and these numbers are then analyzed in more detail. This study uses primary data as its data source. To obtain primary data, researchers distributed questionnaires using a Likert scale with a response interval of 1 to 5 and reliability test. Results: The calculated t value for the Halal Label variable is 2.375. So the calculated t value is 2.375> t table 1.6565. Then the significance level of 0.021 <0.05 can be concluded that H1 is accepted. So it can be concluded that there is a positive and significant influence between the halal label (X1) on purchasing decisions. The t-value for the E-Wom (Electronic Word Of Mouth) variable is 3.715. So the t-value is 3.715 > t table 1.6565. Then the level of significance is 0.000 <0.05 , it can be concluded that H1 is accepted. So it can be concluded that there is a positive and significant influence between E-Wom (Electronic Word Of Mouth) (X2) on purchasing decisions. The t-value for the Customer Loyalty variable is 6.764. So the t-value is 6.764 > t table 1.6565. Then the level of significance is 0.000 <0.05 , it can be concluded that H1 is accepted. So it can be concluded that there is a positive and significant influence between customer loyalty (X3) on purchasing decisions. Conclusion and suggestion: Based on the results of this study on